Bulletin Builder – Software architecture - Lopez, Sebastian; Hernandez, Victor; Giles, James; Swaans, Kees; Le, Tam Thi; Tuan, Manh Lam; Bonilla, Melissa; Londoño, Juan Manuel; Zapata, Emmanuel; Sotelo, Steven (CGIAR, 2025)
This document presents the software architecture for a platform designed to support the creation and dissemination of agroclimatic bulletins, adaptable to the diverse needs of countries, regions, and local contexts. The system aims to provide an accessible and intuitive environment where technical teams can design dynamic templates, configure customized workflows, and generate tailored bulletins for farmers and other beneficiaries. The platform enables flexible template definition so that each region can structure its content according to its specific requirements, including climate conditions, crop status, hazard alerts, recommendations, or even lunar phases. Templates may also incorporate review and approval steps when technical validation is required. A builtin versioning mechanism ensures traceability, supports continuous improvement, and maintains long-term adaptability across evolving use cases. A User-Centered Design approach underpins the system’s development philosophy. Both the pre-designed templates and the platform interface are evaluated through usability testing to ensure that users can navigate and manage the full bulletin production workflow efficiently and with minimal training. During bulletin composition, users can either manually enter content or import information from external services through configurable API connectors, such as weather providers, agricultural advisory services, or communication channels. The system does not store or automatically generate external data; instead, it prioritizes transparency, flexibility, and user control in data handling. Bulletins can be exported in standard dissemination formats, including PDF, PNG, and JPG. The project scope encompasses the complete system development lifecycle: architecture and design, implementation, testing,deployment, and usability assessments to ensure the platform effectively supports human-centered workflows and meets the diverse needs of its users.